Aksjonormatywne, instytucjonalne, kompetencyjne pozory w polskiej edukacji = Axionormative, institutional, cognitional pretences in polish education - Nowak-Dziemianowicz, Mirosława (Zielona Góra: Lubuskie Towarzystwo Naukowe)
Education is this type of social practice, thanks to which the society is secured with continuity and duration as education enables the transmission of culture and allows intergenerational change. Thanks to and by means of education, the development of every human being, each of us, is possible. Education enables learners, developing people to notice and recognise one`s capabilities, aspirations as well as individual needs.
Keywords: edukacja; rozwój; Polska